2010
DOI: 10.1038/hdy.2010.138
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of ovary size and asymmetry in European honeybee workers

Abstract: The molecular basis of complex traits is increasingly understood but a remaining challenge is to identify their co-regulation and inter-dependence. Pollen hoarding in honey bees is a complex trait associated with a well-characterized suite of linked behavioral and physiological traits. In European honey bee stocks bi-directionally selected for pollen hoarding, worker (sterile helper) ovary size is pleiotropically affected by quantitative trait loci that were initially identified for their effect on foraging be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 94 publications
0
24
1
Order By: Relevance
“…Ovariole number is determined in larval honey bees by multiple genotypic, nutritional, and hormonal factors (Evans and Wheeler 1999;Schmidt Capella and Hartfelder 2002;Rueppell et al 2011;and many others). There is a reported positive association between worker ovariole number and tendency to show signs of morphological activation of the ovaries Amdam et al 2006;Tsuruda et al 2008;Traynor et al 2014).…”
Section: Ecdysteroid Titers Were Unrelated To Ovary Activation and Ovmentioning
confidence: 99%
See 2 more Smart Citations
“…Ovariole number is determined in larval honey bees by multiple genotypic, nutritional, and hormonal factors (Evans and Wheeler 1999;Schmidt Capella and Hartfelder 2002;Rueppell et al 2011;and many others). There is a reported positive association between worker ovariole number and tendency to show signs of morphological activation of the ovaries Amdam et al 2006;Tsuruda et al 2008;Traynor et al 2014).…”
Section: Ecdysteroid Titers Were Unrelated To Ovary Activation and Ovmentioning
confidence: 99%
“…Samples contaminated with fat body or gut contents were discarded, and clear samples were dispensed into siliconized microcentrifuge tubes (Thermo Fisher Scientific, Waltham, MA, USA) containing 100 μL of HPLC-grade methanol (Sigma-Aldrich, St. Louis, MO, USA) and stored at − 40°C to permit multiple samples to be analyzed in the same assay run. To determine ovarian status, whole ovaries were removed and rinsed with saline, suspended in 2-3 mL of saline, then assessed using a 5-point scale (Pernal and Currie 2000), in which 0 indicates ovarioles with no signs of swelling, 4 indicates queen-like ovarioles with elongated ooyctes, and intermediate scores are assigned based on degree of swelling and presence of constrictions between follicles, following standard methods (Rueppell et al 2011). Both ovaries were inspected, and a score was given based on the most advanced development observed.…”
Section: Hemolymph and Tissue Collectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly for the reproductive ground plan hypothesis, ovary size of worker honey bees was affected by pln2, pln3 (Wang, Amdam et al, 2009), and pln4 (Ihle, Rueppell et al, in preparation), and hormonal dynamics were affected by pln3 (Ihle, Rueppell et al, in preparation). In all instances, mapping studies of these other traits have revealed additional QTL that usually exceeded the pleiotropic effects of the pln QTL in the specific crosses of the high and low pollen hoarding strains: Three additional QTL for the age of first foraging were identified (Rueppell, Pankiw et al, 2004; Rueppell, 2009), one for sucrose responsiveness (Rueppell, Chandra et al, 2006), and three for worker ovary size (Rueppell, Metheny et al, 2011). One QTL for the age of first foraging ( aff2 ) also showed an effect on worker ovary size and two worker ovary size QTL showed effects on hormonal dynamics (Ihle, Rueppell et al, in preparation).…”
Section: Genetic Architecture Of the Pollen Hoarding Syndromementioning
confidence: 99%
“…Nevertheless, to date QTL in honeybees have been primarily identified for worker specific traits including guarding (Arechavaleta-Velasco and Hunt 2004), stinging (Hunt et al 1998;Guzmán-Novoa et al 2002), foraging (Hunt et al 1995;Page et al 2000, Rüppell et al 2004, hygienic behaviour (Oxley et al 2010), worker-ovary size (Linksvayer et al 2009;Rueppell et al 2011;Graham et al 2011), reproductive traits (Lattorff et al 2007;Oxley et al 2008), larval chalkbrood resistance (Holloway et al 2012) as well as body composition and venom compounds (Mougel et al 2012). We are aware of only three exceptions in which haploid drones have been used, which are on learning behaviour (Chandra et al 2001), sucrose responsiveness (Rueppell et al 2006) and larval Varroa tolerance (Behrens et al 2011).…”
Section: Introductionmentioning
confidence: 99%